Boosting performance through Quick Align solutions - Mohamed Zohdi, Noorharliana; Abdul Halim, Aida Adriana; Bonit, Mazli; Ayoub, Afzan Adilah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Dental simulation training has become a fundamental part of undergraduate dental education. Traditional mounting systems, particularly those using Plaster of Paris (POP), have long been the gold standard. However, POP presents various limitations, such as brittleness, poor retention, difficulty in alignment, time-consuming procedures, and lack of reusability. This paper introduces Quick Align, an innovative simulation model that uses epoxy resin with a magnetic metal attachment to overcome these challenges. This model allows efficient mounting and realignment of extracted human teeth while ensuring strong retention in the phantom head simulator. It also incorporates features for radiograph-taking and improved compatibility with operative protocols like rubber dam application. Survey results revealed significant improvements in stability, efficiency, and user satisfaction, making Quick Align a sustainable, cost-effective, and educationally valuable solution.